2007
DOI: 10.1080/13880200701389011
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity ofPiqueria trinervia., a Mexican Medicinal Plant Used to Treat Diarrhea

Abstract: Intestinal infectious diseases are among the top 10 causes of mortality in Mexico. Children under 5 years of age and adults over 65 years are the most affected; the incidence is greater in rural and indigenous communities. Traditional remedies based on medicinal plants are commonly used; however, the biological activity of many of them has been poorly studied. Thus, we evaluated the antimicrobial activity of the hexane, dichloromethane, ethyl acetate, and methanol extracts of aerial parts and roots of the Piqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…On the other hand, development of drug resistance is becoming serious issue to fight against the diseases [ 15 ]. For instance, few bacteria have developed resistance against available antimicrobial agents which has resulted in significant public health problems [ 16 , 17 ]. Herbal medicine has emerges as a health aid during the last 56 decades and showed the bio prospecting for new plant derived drugs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, development of drug resistance is becoming serious issue to fight against the diseases [ 15 ]. For instance, few bacteria have developed resistance against available antimicrobial agents which has resulted in significant public health problems [ 16 , 17 ]. Herbal medicine has emerges as a health aid during the last 56 decades and showed the bio prospecting for new plant derived drugs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other peaks are probably piquerol isomers and other compounds, such as those identified by Ruiz-Esparza et al. ( 2007 ).…”
Section: Resultsmentioning
confidence: 63%
“…The pulverized materials (760 g) was mixed with Millipore quality water for 24 h. Next, the materials was treated with dichloromethane following the procedures outlined by Ruiz-Esparza et al. ( 2007 ). The remaining solutions were designated as red oil (RO), fractions 1 and 2 (F1 and F2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Over the years, the increase in antibiotic resistance has generated a considerable worldwide public health problem due to successful bacterial adaptation to antibiotics. 3 In addition, it was found that the synthetic antibiotics are not only costly, but also cause some side effects in the treatment of infectious disease. 4 Thus, scientists are forced to search for new antimicrobial substances derived from various natural sources like plants for the treatment of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%